(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The paper presents a wave energy converter concept to harvest energy at Ensenada Bay, Mexico. The study area can be classified as a low energy sea due to the mean wave power being around 10 kW/m; the wave conditions are significant wave height of 0.5 to 2.5 and peak period of 5 to 20 s. The wave energy converter is formed by a torus buoy and anchored to the sea bottom by four connection structures distributed every 90°. The connected structures play a piston role, and their response is leveraged to run a power take-off system, for example, a linear or hydraulic system. This work does not focus on designing the power take-off system; therefore, it is simplified as linear damping, and an iterative process calculates its value. The hydrodynamic buoy study is made on the frequency domain with Nemoh BEM solver and the power absorption on the time domain with the WEC-Sim code. The capture width ratio is used to evaluate the wave energy converter performance and is a key factor in choosing the optimal size. The wave energy converter captures an average of 20% of the available energy and is well-fixed between periods 8 and 16 s. The present study achieves its target: providing a wave energy converter system to operate under site wave conditions.